171 The genetic signature in ischaemic heart disease with myocardial infarction (MI) and significant left ventricular (LV) dysfunction. (6th June 2015) - Rea, Gillian; Petyrka, Joanna; Vieira, Miguel; Buchan, Rachel; Wilkinson, Sam; Walsh, Roddy; John, Shibu; Barton, Paul; Ware, James S; Prasad, Sanjay; Cook, Stuart A
Abstract : The titingene ( TTN ) is a major determinant of myocardial function, its importance in both familial and 'idiopathic' Dilated Cardiomyopathy (DCM) has recently been ascertained. In some instances a second genetic mutation or a physiological perturbation (e.g. pregnancy) may reveal otherwise latent TTN mutation effects. We hypothesise that patients with pronounced LV dysfunction following MI, when controlling for infarct parameters and coronary anatomy, may have a high burden of TTN truncating variants (TTNtvs). We studied a large cohort of post-MI patients prospectively recruited at the Royal Brompton and Harefield NHS Foundation Trust. Gadolinium-enhanced Cardiac Magnetic Resonance was used to characterise cardiac dimensions, function and tissue properties. The size and thickness of MI, wall motion and number of hibernating segments were quantified by two experts blinded to genotype using a standard 17-segment model. Targeted re-sequencing of TTN and other key DCM genes was performed. Genetic variation in DCM genes in 530ethnically matchedhealthy volunteers along with public repositories was used for variant annotation and comparison. Our initial analyses show that out of the 336 post-MI patients, nine (2.7%) had a TTNtv. As hypothesised, TTNtv were significantly enriched in patients with LV ejection fraction (LVEF) <35% (4.6% vs 1.4%, p = 0.01). Patients with a TTNtv had a significantly lower LVEF than those without (31.2 ± 13.9% vs 41.2 ± 14.7%; p = 0.026) Regression models taking into account cardiac, non-cardiac and genetic covariates are in process. These data identify a novel role of large effect size for TTNtv, in post-MI systolic dysfunction. Based on these findings it will be important to explore if genetic stratification of the post-MI patient can inform medical or revascularisation strategies.